LITERASI TEKNOLOGI INFORMASI DAN KOMUNIKASI AGROINDUSTRI RUMAH PANGGUNG DI WOLOAN KECAMATAN TOMOHON BARAT KOTA TOMOHON (Literation of Informationand Communication Technology at Agroindustry â€œRumah Panggungâ€ in Woloan, West Tomohon District, City Tomohon) - Trisilia Makaudis; Ribka M. Kumaat; Leonardus R. Rengkung (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
The purpose of this study was to determine the use of information and communication technology literacy at agroindustry â€œRumah Panggungâ€ in Woloan.Â  The data used in this study were primary and secondary data. Samples were taken as many as 8 businesses with â€œCVâ€ status and selected by using purposive sampling.Data Analysis used was quantitative descriptive analysis. Variables were measured in 5 (five) categories, namely Very Often (SS), Frequently (S), Rarely (J), Very Rarely (SJ), Never (TP) in association with the concept of literacy in the aspects of define, access, manage, integrate, evaluate, create and communicate.The results showed that information and communication technology literacy was often used in several aspects, namely marketing, production, communication, and financial reporting, through the use of social media, email and websites.Keywords: information and communication technology, â€œrumah panggungâ€